Kajian Introduksi Teknologi Rumput Laut dalam Upaya Peningkatan Pendapatan Kelompok Tani di Kelurahan Bungkutoko Kecamatan Abeli Kota Kendari - Fausayana, Ine (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2012)
Long-Range target this research is a technological introduction of seaweed with system pluck process and sell in the effort increase earnings of farmer group in Sub-District Of Bungkutoko District Of Abeli Town of Kendari Special Target this research is ( 1). Measuring improvement of productivity and earnings of conducting result and handling of seaweed after by using net keramba float, ( 2). To know earnings of society before and after the existence of technological introduction in the form of processing of seaweed result become multifariously of product, In The Year I technological Introduction to be applied at conducting is making of seaweed construction method of long line by using system of keramba net float functioning to arrest;detain to fall or loss of seaweed go out to sea effect of wave or come down with. With this technology is expected can increase product and productivity. Analysis the used is Analysis Earnings, that is Budget of Partial(Partial Budget Analysis). Research location in Sub-District Of Bungkutoko District Of Abeli Town of Kendari.